Lung Volume Changes in Stable Preterm Infants Weaned From Nasal CPAP to High FlowTake-home Points - Vanessa L. Büchler, MD; Vincent D. Gaertner, MD; Janine Thomann, MD; Dirk Bassler, MD; Christoph M. Rüegger, MD (CHEST Pulmonary)
Background: Weaning preterm infants off nasal CPAP (nCPAP) using nasal high-flow therapy has gained popularity. The effects of such a weaning strategy on lung volumes are unclear. Research Question: How does the transition from nCPAP to high flow and varying flow levels affect lung volumes in stable preterm infants? Study Design and Methods: This was a prospective cohort study in infants 30 to 35 weeks’ postmenstrual age. After a baseline period on nCPAP 5 cm H2O, infants were switched to high flow 8 L/min for 30 minutes. The flow level was reduced by 2 L/min every 30 minutes to a minimum of 2 L/min and subsequently increased to the initial level of 8 L/min, followed by another nCPAP period. Using electrical impedance tomography, end-expiratory lung impedance as a proxy for end-expiratory lung volume (EELV) and cardiorespiratory parameters were recorded at each flow level and compared with baseline. Results: Overall, 8,438 breaths from 19 infants were analyzed. EELV changed significantly during the study (P = .002), which was mainly attributable to a loss of EELV when high flow was reduced to 6 and 4 L/min and re-escalated to 4, 6, and 8 L/min. Apart from a reduction in minute ventilation (P = .004), no other significant changes were found in electrical impedance tomography ventilation parameters. Alterations in lung volume were accompanied by an increase in heart rate (P = .02) and a decrease in peripheral oxygen saturation/Fio2 ratio (P < .001). Interpretation: The results of this study indicate that the transition from nCPAP to high flow is likely to result in a reduced EELV, accompanied by physiological responses in heart rate and oxygenation. Despite a stepwise escalation to preweaning flow levels, we found that only partial recovery of lung volume losses was achievable with high flow. Clinical Trial Registration: ClinicalTrials.gov; No.: NCT05237622; URL: www.clinicaltrials.gov